Survey of blockchain:principle,progress and application - Shiqin ZENG; Ru HUO; Tao HUANG; Jiang LIU; Shuo WANG; Wei FENG (Tongxin xuebao)
Blockchain is a kind of distributed ledger technology that upgrades to a complete storage system by adding logic control functions such as intelligent contracts.With the changes of its classification,service mode and application requirements,the core technology forms of Blockchain show diversified development.In order to understand the Blockchain ecosystem thoroughly,a hierarchical technology architecture of Blockchain was proposed.Furthermore,each layer of blockchain was analyzed from the perspectives of basic principle,related technologies and research progress in-depth.Moreover,the technology selections and characteristics of typical Blockchain projects were summarized systematically.Finally,some application directions of blockchain frontiers,technology challenges and research prospects including Smart Cities and Industrial Internet were given.